2009
DOI: 10.1371/journal.pone.0006953
|View full text |Cite|
|
Sign up to set email alerts
|

Insulin Gene Expression Is Regulated by DNA Methylation

Abstract: BackgroundInsulin is a critical component of metabolic control, and as such, insulin gene expression has been the focus of extensive study. DNA sequences that regulate transcription of the insulin gene and the majority of regulatory factors have already been identified. However, only recently have other components of insulin gene expression been investigated, and in this study we examine the role of DNA methylation in the regulation of mouse and human insulin gene expression.Methodology/Principal FindingsGenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
193
4
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(216 citation statements)
references
References 49 publications
9
193
4
3
Order By: Relevance
“…Our findings indicate that this method provides a biomarker for detecting β cell loss in prediabetic mice during progression of diabetes, and suggest it does the same in patients with new-onset T1D. Kuroda et al (26) previously identified demethylation of CpG sites in the insulin promoter, consistent with the notion that methylation of promoters is a mechanism for controlling tissuespecific gene expression. However, our analysis targeted differentially methylated CpG dinucleotides in the Ins1 gene in mice and the Ins gene itself in humans.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings indicate that this method provides a biomarker for detecting β cell loss in prediabetic mice during progression of diabetes, and suggest it does the same in patients with new-onset T1D. Kuroda et al (26) previously identified demethylation of CpG sites in the insulin promoter, consistent with the notion that methylation of promoters is a mechanism for controlling tissuespecific gene expression. However, our analysis targeted differentially methylated CpG dinucleotides in the Ins1 gene in mice and the Ins gene itself in humans.…”
Section: Discussionsupporting
confidence: 83%
“…Aging, nutrition and sedentary lifestyle have been associated with epigenetic changes characteristic of type-2 diabetes [ 54 ]. DNA methylation have been shown to vary in diabetic vs. non-diabetic subjects, therefore this association strongly stresses for the existence of an epigenetic basis in the pathogenesis of type-2 diabetes [ 55 ].…”
Section: ' Dna Methylation-based ' Diseasesmentioning
confidence: 99%
“…Tissue-specific level of CpG methylation is found for example in promoters of leptin, pro-opiomelanocortin (precursor for melanocyte-stimulating hormone (a-MSH), ACTH and b-endorphine) and insulin correlating to the corresponding tissue-specific expression levels (for review, see McAllister). 39,40 That changes in DNA methylation can occur postnatally can be exemplified by increase in CpG methylation of the key metabolic transcriptional regulator peroxisome proliferator-activated receptor-a (Ppar-a) by folate supplementation in young rodents. 41 In fact, mice on high-fat diet developed hypomethylation in the satiety-receptor melanocortin-4 receptor, 42 whereas neonatal overfeeding rats, and rats obese because of overfeeding in small litters, developed hypermethylation of the satiety-mediator pro-opiomelanocortin in hypothalamus.…”
Section: Epigenetic Factors In Obesitymentioning
confidence: 99%